2020
DOI: 10.1155/2020/6398165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Nanoparticles on Biofilm Formation and EPS Production of Multidrug-Resistant Klebsiella pneumoniae

Abstract: Antibiotic resistance against present antibiotics is rising at an alarming rate with need for discovery of advanced methods to treat infections caused by resistant pathogens. Silver nanoparticles are known to exhibit satisfactory antibacterial and antibiofilm activity against different pathogens. In the present study, the AgNPs were synthesized chemically and characterized by UV-Visible spectroscopy, scanning electron microscopy, and X-ray diffraction. Antibacterial activity against MDR K. pneumoniae strains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 24 publications
5
60
1
Order By: Relevance
“…Moreover, AgNPs synthesized by Cryphonectria sp. showed antibacterial activity against various human pathogenic bacteria, including S. aureus , Klebsiella pneumoniae , E. coli , Salmonella typhi and Candida albicans [ 9 , 30 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ].…”
Section: Nanomaterials As New Potential Antibioticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, AgNPs synthesized by Cryphonectria sp. showed antibacterial activity against various human pathogenic bacteria, including S. aureus , Klebsiella pneumoniae , E. coli , Salmonella typhi and Candida albicans [ 9 , 30 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ].…”
Section: Nanomaterials As New Potential Antibioticsmentioning
confidence: 99%
“…Cells included in the biofilm differ physiologically and morphologically from the free-living cells of the same species. The complex process of biofilm formation consists of several characteristic stages, such as adhesion, formation, maturation and its decay [ 77 , 78 , 79 , 80 , 81 ]. Biofilms are settled populations of one or more species of microorganisms that are attached to a biotic or abiotic solid surface or are formed at the interface [ 77 , 78 , 79 , 80 , 81 ].…”
Section: Nanomaterials As New Potential Antibioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Size and shape influence the antibacterial effect of silver nanoparticles: Hong et al reported a higher antibacterial effect to E. coli of silver nanocubes to spheres and wires [70]; while their antimicrobial activity decreases with increasing particles size, as reported by Raza and colleagues [48], [71]. Many studies suggest an AgNPs role in inhibiting bacterial biofilm formation and EPS (Extracellular polymeric substances) production, mainly when associated with the plant-derived drug-like quercetin [72], [73].…”
Section: Metallic Nanoparticles: Gold and Silver Nanoparticlesmentioning
confidence: 92%